2013
DOI: 10.1101/gr.154872.113
|View full text |Cite
|
Sign up to set email alerts
|

Sumoylation at chromatin governs coordinated repression of a transcriptional program essential for cell growth and proliferation

Abstract: Despite numerous studies on specific sumoylated transcriptional regulators, the global role of SUMO on chromatin in relation to transcription regulation remains largely unknown. Here, we determined the genome-wide localization of SUMO1 and SUMO2/3, as well as of UBC9 (encoded by UBE2I ) and PIASY (encoded by PIAS4), two markers for active sumoylation, along with Pol II and histone marks in proliferating versus senescent human fibroblasts together with gene expression profiling. We found that, whereas SUMO alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
141
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(164 citation statements)
references
References 55 publications
22
141
0
Order By: Relevance
“…The distribution of Sumo strongly resembles the genomic distribution of Sumo in mammalian cells (Neyret-Kahn et al 2013). There have been conflicting reports as to how Sumo affects transcription at these genes in mammals; one study reported that Sumo promotes their transcription (Liu et al 2012), whereas another study found that Sumo is inhibitory (Neyret-Kahn et al 2013). The reason for these differences is unclear, but could be technical (Neyret-Kahn et al 2013).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The distribution of Sumo strongly resembles the genomic distribution of Sumo in mammalian cells (Neyret-Kahn et al 2013). There have been conflicting reports as to how Sumo affects transcription at these genes in mammals; one study reported that Sumo promotes their transcription (Liu et al 2012), whereas another study found that Sumo is inhibitory (Neyret-Kahn et al 2013). The reason for these differences is unclear, but could be technical (Neyret-Kahn et al 2013).…”
Section: Discussionmentioning
confidence: 81%
“…There have been conflicting reports as to how Sumo affects transcription at these genes in mammals; one study reported that Sumo promotes their transcription (Liu et al 2012), whereas another study found that Sumo is inhibitory (Neyret-Kahn et al 2013). The reason for these differences is unclear, but could be technical (Neyret-Kahn et al 2013). These two studies did not identify the Sumo target at these genes, making it difficult to interpret their different findings.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, knockdowns of Ubc9 or the SUMO E1 subunit SAE2 in human cells severely reduced the cell proliferation rate but did not arrest cells in a specific cell cycle stage [22,23]. This could be explained by SUMO having essential functions during all cell cycle phases in mammalian cells, not just during the G2/M transition.…”
Section: Twenty Years Of Sumo Research In Cell Cycle Controlmentioning
confidence: 98%
“…Chromatin immunoprecipitation studies in yeast revealed the association of SUMO and the SUMO E2 with constitutively active and inducible promoters (Rosonina et al, 2010). Additionally, a recent elegant and comprehensive study was performed in proliferating and senescent human fibroblasts using chromatin immunoprecipitation to identify genome-wide association sites of several SUMO isoforms, SUMO machinery enzymes, different histone and chromatin marks, and RNA polymerase II (Pol II) and combined this with genome-wide expression profiling (Neyret-Kahn et al, 2013). This study revealed the association of either SUMO1 or SUMO2 with the transcriptional start sites (TSSs) of approximately 7,700 genes, and of these genes, 67% were significantly expressed.…”
Section: Target Modification By Sumo: Implications and Functionsmentioning
confidence: 99%